Evaluating the effectiveness of care integration strategies in different healthcare systems in Latin America: the EQUITY-LA II quasi-experimental study protocol. Issue 7 (31st July 2015) - Vázquez, María-Luisa; Vargas, Ingrid; Unger, Jean-Pierre; De Paepe, Pierre; Mogollón-Pérez, Amparo Susana; Samico, Isabella; Albuquerque, Paulette; Eguiguren, Pamela; Cisneros, Angelica Ivonne; Rovere, Mario; Bertolotto, Fernando
Abstract : Introduction: Although fragmentation in the provision of healthcare is considered an important obstacle to effective care, there is scant evidence on best practices in care coordination in Latin America. The aim is to evaluate the effectiveness of a participatory shared care strategy in improving coordination across care levels and related care quality, in health services networks in six different healthcare systems of Latin America. Methods and analysis: A controlled before and after quasi-experimental study taking a participatory action research approach. In each country, two comparable healthcare networks were selected—intervention and control. The study contains four phases: (1) A baseline study to establish network performance in care coordination and continuity across care levels, using (A) qualitative methods: semi-structured interviews and focus groups with a criterion sample of health managers, professionals and users; and (B) quantitative methods: two questionnaire surveys with samples of 174 primary and secondary care physicians and 392 users with chronic conditions per network. Sample size was calculated to detect a proportion difference of 15% and 10%, before and after intervention (α=0.05; β=0.2 in a two-sided test); (2) a bottom-up participatory design and implementation of shared care strategies involving micro-level care coordination interventions to improve the adequacy of patient referral and information transfer. Strategies are selected through a participatory process by the local steering committee (local policymakers, health care network professionals, managers, users and researchers), supported by appropriate training; (3) Evaluation of the effectiveness of interventions by measuring changes in levels of care coordination and continuity 18 months after implementation, applying the same design as in the baseline study; (4) Cross-country comparative analysis. Ethics and dissemination: This study complies with international and national legal stipulations on ethics. Conditions of the study procedure were approved by each country's ethical committee. A variety of dissemination activities are implemented addressing the main stakeholders. Registration No.257 Clinical Research Register of the Santa Fe Health Department, Argentina.